A Comprehensive Oral Intake Evaluation Tool (the Kuchi-kara Taberu Index) Facilitated Functional Eating Rehabilitation: A Case Report in a Frail Older Patient with Malnutrition and Suspected Iatrogenic Sarcopenia. (1st April 2022) - Hidaka, Yoshifumi; Watanabe, Satomi; Nishikawa, Yumiko; Irie, Iroha
Frail older hospital patients are susceptible to malnutrition and iatrogenic sarcopenia. This can be linked to the decreased appetite and oral intake that can arise in largely bed-bound patients who do not get up even for rehabilitation and meals. The KT index was devised as an easy-to-use evaluation tool to address oral intake issues, and it has potential utility for expediting a multidisciplinary comprehensive rehabilitation program. To our knowledge, no reports have described real-world evidence on multidisciplinary team interventions with this tool. Herein, we report the case of a frail older patient whose oral intake improved following a KT Index-based intervention.